A Pan-Inhibitor of Phosphate Transporters AP306 in Hemodialysis Patients - Li Wang; Li Zuo; Ming Shi; Leyi Gu; Kunling Ma; Pei Wang; Yu Wang; Qun Luo; Menghua Chen; Ping Zhang; Hongli Jiang; Guisen Li; et al. (Kidney International Reports)
Introduction: Hyperphosphatemia in patients undergoing dialysis is not well-controlled. AP306 is a pan-inhibitor of phosphate transporters, designed to block the active uptake of phosphate through the gastrointestinal tract. Methods: In this phase 2 randomized, active-controlled, open-label study, hemodialysis patients with serum phosphate between 5.5 and 9.0 mg/dl were randomized to receive either AP306 or sevelamer carbonate for 12 weeks. The primary outcome was the change in serum phosphate levels from baseline until the therapy ceased. AP306 was initiated at 75 mg and adjusted stepwise to 125 mg and 150 mg orally thrice daily every 4 weeks, to maintain serum phosphate between 3.5 and 5.5 mg/dl. Sevelamer levels were adjusted using the same criteria and frequency. Results: A total of 27 patients were randomized to receive AP306 and 28 to receive sevelamer. At the end-of-treatment, both AP306 and sevelamer resulted in a significant decrease from baseline in serum phosphate by 2.51 mg/dl (95% confidence interval [CI]:−3.07 to −1.92; P < 0.001) and 1.08 mg/dl (95% CI: −1.58 to −0.59), respectively. The proportions of patients achieving the recommended range as per the Kidney Disease: Improving Global Outcomes guidelines (2.5–4.5 mg/dl) were about 20% higher in AP306 than in sevelamer, starting from treatment week 5. The most reported adverse events (AEs) associated with AP306 were gastrointestinal disorders (51.9%), most of which were mild to moderate diarrhea (44.4%). Conclusion: AP306 monotherapy significantly reduced serum phosphate levels and substantially improved the serum phosphate control rate in hemodialysis patients with hyperphosphatemia. AP306 was safe and well-tolerated.